Challenges and Strategies of Muslim in the Era of Society 5.0 in Indonesia - Mulauddin, Aforisma (International Conference on Islamic Studies, 2022)
Human power in the era of society 5.0 has been replaced by machines automatically. Humans must always adapt because technology is currently part of humans themselves, it is marked by the development of the era of society starting from the era of 1.0 Hunting and Gathering, 2.0 Agricultural, 3.0 Industrial, 4.0 Information and 5.0 New Society. (Convergence Virtual and Physical Worlds). Current technological advances are the Internet of Things (IoT) in the form of Artificial Intelligence, Big Data, Marketplace, Fintech and other. This creates a challenge for Muslims who need to find a strategy to deal with it. This is library research using qualitative methods with literature review examining several research results from various journals and books or other primary sources. So that this study gets a result that the challenges of Muslims in the era of society 5.0 are the amount of hoax information circulating, the influence of outside culture on the culture of the Indonesian nation and the demographic bonus as the largest Muslim. In overcoming this, what needs to be done is to validate the news sent and received, make Islam a lifestyle and strengthen Islamic education as a basic of da'wah in Muslim families.